Guiding the design of lessons by using the MAPLET framework: matching aims, processes, learner expertise and technologies - Ifenthaler, Dirk; Gosper, M. (Springer, 2013)
This paper introduces the MAPLET framework that was developed to map and link teaching aims, learning processes, learner expertise and technologies. An experimental study with 65 participants is reported to test the effectiveness of the framework as a guide to the design of lessons embedded within larger units of study. The findings indicate the potential of the MAPLET framework and reinforces the need to take a fresh approach to the design and development of curriculum that makes more effective use of the diminishing time available. It provides a conceptual model and working procedure that places the learner and the process of learning at the forefront of decisions.